Cooperative Development: Sustainability Agricultural Planning Viewed Through Cooperative Equilibrium Management Theory in Togo, Africa - Berge, Simon T.; Bokoumbo, Koudima; Johnson, Kuawo Assan; Yabi, Jacob Afouda; Yegbemey, Rosaine Nerice (Frontiers in Sustainable Food Systems, 2021)
Cooperative economics looks at market failures as areas for improvement and development. The cooperative development process, however, requires member engagement and cohesion according to the Cooperative Management Equilibrium Theory. This cohesion requires an awareness and understanding by the cooperative members of the market failures. How and who determines the market failures is at question. This article looks at the effects of government agricultural planning on economic, environmental and social sustainability as implemented by individual and co-operative producers. The questions we ask in this paper is how does a focus on economic development push back against social and environmental sustainability within the agricultural sector in Togo? Does member cohesion within a cooperative represent a form of Polanyian countermovement through social action moving development away from a Sen style austere mode of development toward the friendly development approach? Utilizing Deep Participatory Indicator-Based (DPIB) approach this paper examines the economic, environmental and social indicators within two prefectures in the Plateaux Region of Togo. Indicators were separated to show the differences between individual or cooperative producers. For cooperative producers it was anticipated that a greater emphasis on social and environmental sustainability would be created through cohesive social action. This study found that the emphasis on economic development included in government planning built cohesion within cooperative membership focused on economic indicators rather than environmental or social development.